Are the remnants of old-growth mountain forests always relevant to inspire close-to-nature forest management and efficient biodiversity conservation?. (March 2023) - Larrieu, Laurent; Burri, Sylvain; Corriol, Gilles; Gouix, Nicolas; Ladet, Sylvie; Laroche, Fabien; Maillé, Sophie; Py-Saragaglia, Vanessa; Savoie, Jean-Marie; Brin, Antoine
Abstract: Primary and old-growth forests have been identified as a high priority for biodiversity conservation and for identifying benchmarks for biodiversity-friendly forestry. However, they remain rare and not randomly distributed across Europe, concentrated mainly in the boreal zone or in mountainous areas such as the Pyrenees where both ancient (i.e. with a high degree of continuity) and mature (i.e. with old-growth attributes) forests (hereafter AMFs) have been identified and accurately delimited on the French side of the border. Can these AMF remnants provide suitable benchmarks and insure biodiversity conservation? This study aimed to (i) identify factors that explain the current location of AMFs; (ii) assess the potential of these AMFs as reference ecosystems; and (iii) discuss the relevance of the current AMF network for biodiversity conservation. We used a set of 10, 344 1 ha-plots, described by 10 metrics for both abiotic conditions and the socio-economic context, to compare AMFs with both forests that are ancient but not mature, and recent forests. AMFs significantly differed from other forests for most of the variables tested, but effect sizes were rather weak, with the exceptions of the occurrence of late frost, exposition and ownership type. Our study provides important insights for biodiversity conservation beyond the case of the northern slope of the Pyrenees. Indeed, our results clearly show that broad-scale patterns require complementary investigations at a regional scale to better understand the influence of past-human activity on the spatial distribution of reference ecosystems. We also illustrate the added value of including geological features and plant communities in the analysis of ecological representativeness of networks dedicated to biodiversity conservation. Highlights: Both ancient and mature forests cover about 4 % of forest area in the French Pyrenees. We looked for factors explaining their occurrence. Ownership type, late frost and exposition are the most significant factors. The current network cannot fully ensure the conservation of forest biodiversity. Nor can it inspire biodiversity-friendly management for all types of forests